2013
DOI: 10.3133/sir20135190
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of methane in groundwater of south-central New York State, 2012-systematic evaluation of a glaciated region by hydrogeologic setting

Abstract: supported the study. Elizabeth Nystrom assisted with sampling and sampling equipment in the field, including the field measurement of methane. Richard Reynolds and Carolyn Van Alstyne also assisted with field sampling, and Patrick Phillips prepared statistical and quality-assurance analyses. Martyn Smith and Douglas Freehafer provided geographic information system support that included processing of lidar imagery, and generation and processing of stream network and topographic information that facilitated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
91
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(112 citation statements)
references
References 22 publications
19
91
2
Order By: Relevance
“…The highly saline sodium chloride brines and overlying groundwaters of intermediate salinity generally are present 1,000 feet or more below the surface (Feth, 1965;Heisig and Scott, 2013). Such brine-influenced waters commonly are produced from gas or oil wells (Dresel and Rose, 2010;Hayes, 2009;Halusczak and others, 2013), and may affect water quality of springs and domestic-supply wells (Llewellyn, 2014;Siegel and others, 2015).…”
Section: Conceptual Hydrogeochemical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly saline sodium chloride brines and overlying groundwaters of intermediate salinity generally are present 1,000 feet or more below the surface (Feth, 1965;Heisig and Scott, 2013). Such brine-influenced waters commonly are produced from gas or oil wells (Dresel and Rose, 2010;Hayes, 2009;Halusczak and others, 2013), and may affect water quality of springs and domestic-supply wells (Llewellyn, 2014;Siegel and others, 2015).…”
Section: Conceptual Hydrogeochemical Settingmentioning
confidence: 99%
“…These trace cations can also appear locally as pure carbonate phases. Over the range of pH, the SI values for siderite, , plus median composition of brine from oil and gas wells in western Pennsylvania (Dresel and Rose, 2010) and flowback water from Marcellus Shale gas wells (Hayes, 2009). Symbols for groundwater scaled by specific conductance.…”
Section: Water-quality Variations and Water-rock Interactionsmentioning
confidence: 99%
“…major stream feature. The proximity to streams was used to differentiate valley from upslope sample locations, with greater methane concentrations expected in valley areas because these areas are more likely to represent regional groundwater discharge areas, and hence groundwater with a longer residence time in the subsurface and greater potential to interact with strata producing methane (Heisig and Scott 2013). The present study, however, found significantly elevated methane levels in upland areas (i.e., >300 m from stream feature) compared to valley areas.…”
Section: Well Water Geochemistrymentioning
confidence: 64%
“…Several recent studies have investigated the spatial patterns of regional groundwater methane distribution using statistical techniques, and it has generally been found that dissolved methane in well water was best correlated with groundwater geochemistry (Molofsky et al 2013;McPhillips et al 2014) with some studies also reporting significantly higher concentrations of methane encountered in lowland or valley areas compared to upland or hill top areas (Molofsky et al 2013;Heisig and Scott 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The groundwater quality in private wells can be impacted by myriad factors, including the geological source formation, topography (valley or upland) of the well site, groundwater flow path, recent amount of precipitation, productivity and the amount of daily water usage, other potential contamination sources (e.g., sewage, road spills of chemicals), wellbore/casing integrity, and well depth of private wells. For example, methane levels in groundwater (GW) have been found to be statistically higher in valleys and/or under confined groundwater conditions (Heisig and Scott, 2013). Uplands are groundwater recharge areas, while valleys tend to be discharge areas located at the end of flowlines with more evolved geochemistry.…”
Section: Introductionmentioning
confidence: 99%